Консолидация демократии: проблема определения понятия - Титарь, И. (Социология: теория, методы, маркетинг, 2008)
The research is devoted to analysis of the “consolidation of democracy” definition problem. Although it is one of the major notions of transitological literature, its meaning is still ambiguous and debatable. The etymological and historical aspects of understanding the meaning of “consolidation” are considered in the article. The main definitions of the notion “consolidation of democracy” are discussed. Different ap proaches are considered in order to facilitate their systematization and help to find the most adequate and practically useful definition of the concept. The attempt to underline differences in the term “consolidation” understanding in Ukrainian and Russian, on the one hand, and in English, on the other hand, is rather helpful in search for adequate definition. The authors’ definition of the consolidation of democracy isn’t intended either to deepen or to extend its interpretation. Besides, it’s rather aimed to point out and try to avoid the main errors in its usage, particularly regarding the task of its opera tionalization within the framework of sociological empirical research.